Oral health related quality of life in stroke survivors at community-based rehabilitation centre: A pilot study - Tew, In Meei; Goo, Chui Ling; Said, Shahida Mohd; Zahari, Hafizul Izwan; Ali, Noor Amalina; Masawi, Fatin Athirah; Abdul Aziz, Aznida Firzah; Mohd Dom, Tuti Ningseh (Makara Journal of Health Research, 2020)
Background: Despite being a common problem, long-term disability following stroke often improves after survivors receive regular rehabilitative therapy. This study aimed to assess the oral health-related quality of life (OHRQoL) of stroke survivors who had access to a community-based rehabilitation centre after hospital discharge. Methods: Dentate post-stroke patients receiving regular rehabilitative care with slight to moderate dependency (Barthel Index >70) and without severe cognitive impairment were involved in this study. The OHRQoL parameters were measured using the Oral Health Impact Profile-14 (OHIP-14) and EuroQol five dimensions (EQ-5D-5L) questionnaires. Results: Thirty one patients were recruited in this study. Majority of the patients hardly ever or never had problems in all functional, physical, psychological and social domains, including eating discomfort and having to avoid eating, difficulty in chewing food and presumably having bad breath (58.1%, 61.3% and 71.0% respectively). Other than gender, age, ethnicity, co-morbidities and oral hygiene practices, education level was the only variable found to significantly affect patients’ OHRQoL (p = 0.028). Most of the patients had no or slight problem(s) in self-care (87.1%) and carrying out usual activities (57.1%), pain/discomfort (3.2%) and anxiety/depression (6.5%). Conclusion: Stroke survivors under regular rehabilitative care perceived have good oral health-related quality of life.